Динамика морфометрических показателей пораженной кожи при ограниченной склеродермии до и после комплексной терапии - Романенко, К.В. (Таврический медико-биологический вестник, 2009)
Морфологічно та морфометрично досліджували біоптати ураженої шкіри 39 хворих

на різні форми обмеженої склеродермії після комплексного лікування. Визначали

питомі об’єми: судин мікрогемоциркуляторного русла, клітинних інфільтратів

дерми, еластичних і патологічно змінених колагенових волокон, вимірювали

товщину епідермісу. С целью об’єктивної оцінки лікувального патоморфозу

обчислювали індекси регресу патологічних змін основних структурних компонентів

шкіри при різних формах обмеженої склеродермії. Згідно значення сумарного

показника різновиди дерматоза розподілялись таким чином: 1) осередкова форма

обмеженої склеродермії в стадії набряку (2,75); 2) осередкова форма в стадії

склерозу (1,45); 3) склероатрофічний ліхен (1,22); 4) атрофодермія Пазіні-П’єріні

(1,04). Ні при жодному з клінічних різновидів обмеженої склеродермії після

лікування не вдається досягнути повного встановлення структурних компонентів

шкіри. Кількісна і якісна характеристика структурно-функціонального стану шкіри

може служити для: 1) початкової оцінки активності і тяжкості патологічного

процесу; 2) об’єктивної оцінки терапії, що здійснювалась; 3) висвітлення

механізмів впливу методів лікування на окремі компоненти патологічного процесу в

шкірі хворих на обмежену склеродермію. Biopsies for the histological and morphometric examination were taken from the

lesioned skin of 39patients with various forms of morphea following their combined

treatment. Their morphological study included measurement of the specific volume of

microvessels in the capillary vasculature, dermal cell infiltrates, elastic and

pathologically altered collagen fibers; the thickness of epidermis was also measured.

Indices of regressive pathological changes in main skin structures attending various

forms of morphea were calculated and used to objectively assess therapeutic

efficiency of the treatment. The integrated index provided a tool for the classification of

different clinical variants of dermatosis into the following groups: 1) localized forms of

morphea at the stage of oedema (2,75), 2) localized forms of morphea at the

compaction stage (1,45), 3) lichen sclerosus et atrophicus (1,22), 4) Pasini-Pierini’s

atrophoderma (1,04). None of the clinical variants of morphea was completely

corrected by the applied treatment in terms of restoration of structural skin

components. It is concluded that quantitative and qualitative characteristics of

structural and functional skin status may be used to 1) estimate baseline activity and

severity of the pathological process, 2) objectively evaluate clinical efficiency of

therapy, and 3) elucidate the mechanisms and magnitude of effects of the treatment

on individual components of the pathological process in the skin of localized

scleroderma patients.